Analisis Semiotika Roland Barthes Dalam Pertunjukan Randai Sanggar Mudo Barapi Di Kota Solok - Nadya Khairunnisa; Yusuf Afandi (Lembaga Pengembangan Kinerja Dosen, 2023)
Indonesia has a diversity of ethnic groups. a country that has a lot of cultural diversity in each region, this can be expressed in the dances of each culture. Through music and movement, they produce a dance that discusses the diversity and richness of Indonesian culture. One of the old arts that illustrates this is Minangkabau randai, Minangkabau randai originated from the performance of the younger generation of society. This type of research uses qualitative methods with a semiotic analysis model by Roland Barthes. The data collection was carried out using documentation, interviews and observations. Based on the results of research conducted on